Разведки в Раздольненском р-не Крыма - Юрочкин, В.Ю.; Колтухов, С.Г. (Археологічні дослідження в Україні, 2010)
Information on archaeological sites uncovered during the 2009 archaeological prospecting in Rozdolne Region of the Crimea is given.